2018
DOI: 10.3390/socsci7080134
|View full text |Cite
|
Sign up to set email alerts
|

From Active Aging to Active Citizenship: The Role of (Age) Friendliness

Abstract: The concept of 'Active Aging' emerged in the 1990s, reflecting a growing emphasis on the relationships between health, participation, aging, and independence. The concept focuses on encouraging the participation of older adults in society and it recognizes the competence and knowledge that older people possess. The Active Aging discourse developed as a broad political response to demographic aging, one which promotes a cultural shift in what 'old age' may mean, by providing older people with new roles. The ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 65 publications
1
36
0
10
Order By: Relevance
“…The sense of community ownership and involvement in site planning and management, social activities [7,32,39,42,65,79,80,83,86,[103][104][105][106] Social class [23] Social support/ community life facilities and services [40,51,54,63] Education, learning, employment and volunteering, [40] Social capital/ social trust/ Social cohesion [63] Cultural Environment…”
Section: Placementioning
confidence: 99%
“…The sense of community ownership and involvement in site planning and management, social activities [7,32,39,42,65,79,80,83,86,[103][104][105][106] Social class [23] Social support/ community life facilities and services [40,51,54,63] Education, learning, employment and volunteering, [40] Social capital/ social trust/ Social cohesion [63] Cultural Environment…”
Section: Placementioning
confidence: 99%
“…Based on the paradigm of AFCC [ 5 , 7 ], the theoretical approach of AA [ 3 , 71 , 72 , 73 , 74 ] was referred to in 54.5% of studies [ 60 , 61 , 65 , 66 , 68 , 70 ], and the approach of healthy ageing [ 4 ] was referred to in 54.5% of cases [ 60 , 61 , 63 , 66 , 68 , 69 ]. Additionally, in 36.4% of retained publications [ 60 , 61 , 66 , 68 ] the theoretical approaches of AA and healthy ageing were cited together [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The academic literature shows that a lack of consensus as to the conceptual and methodological definition of interventions has affected the viability of broader practical implementation and the potential benefits of interventions [ 26 , 34 ]. In this respect, the retained studies have not specifically contributed to progress in defining the concept of intervention, or to the production of theoretical models under the AFCC and AA paradigm [ 7 , 72 ]. In fact, one third of articles did not refer to the theoretical approaches of active and healthy ageing [ 62 , 64 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both European and Croatian Gerontological findings have confirmed that one cannot neglect the codependence of an elderly person and their health preservation regarding the community one lives and is productive in. Functionally, capable older persons are extremely productive community members [36]. They can be used to share and transfer their knowledge, skills, and work experience onto the younger, but also older generations Old age is a time when life is characterized by new spiritual dimensions and advantages that did not exist in one's youth.…”
Section: Discussionmentioning
confidence: 99%
“…They can be used to share and transfer their knowledge, skills, and work experience onto the younger, but also older generations Old age is a time when life is characterized by new spiritual dimensions and advantages that did not exist in one's youth. Active healthy aging also includes one's ability to adjust to new circumstances, knowledge and constant learning and discovering of the advantages of the aging process and old age itself [36].…”
Section: Discussionmentioning
confidence: 99%